Kajian Terjemahan Teks Pidato Soekarno Lahirnya Pancasila: Unit Bahasa, Teknik, dan Kualitas Penerjemahan Indonesia-Arab - Elisa Dwivita Putri; Muhammad Yunus Anis (Kementerian Sekretariat Negara Republik Indonesia, 2026)
This study aims to assess the quality of the language units and translation techniques used in Soekarno’s speeches, which have significant historical and linguistic value. A qualitative method was employed in this research. This research employs three techniques: sampling, data collection, and data analysis. The sampling technique used was non-probability sampling. Documentation is used for data collection. Furthermore, the Miles and Huberman data analysis model was applied to analyze the data. The findings reveal language units in the research object: words, phrases, clauses, sentences, and discourse. Additionally, 15 out of 18 translation techniques were identified as being employed. The translation quality assessment also yielded high scores, indicating that the translation of the research object demonstrates good quality in terms of accuracy, acceptability, and readability.